2022
DOI: 10.1007/s12063-022-00319-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The impact of omni-channel collaborative marketing on customer loyalty to fresh retailers: the mediating effect of the omni-channel shopping experience

Abstract: The relationship between collaborative marketing and customer loyalty has attracted attention in retail practice. However, in omni-channel retail, the impact mechanism of the two needs to be further defined academically. Based on the theoretical analysis of the stimulus-organism-response (SOR) framework, this paper systematically creates a research model of the impact of omni-channel collaborative marketing on new customer loyalty. It leads an empirical study using structural equation modeling with survey data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…to do research, why the big name Panasonic, which has been present in Indonesia for a long time, can't boost its high market share gain, can only stay in the top 5 positions. In fact, Panasonic has entered the electronic market in Indonesia earlier than other brands.Marketing managers in retail organizations usually devote time and effort to analyze the right promotions and products to maintain customer loyalty, so that the organization can be positioned properly in the market [3]. Sometimes, other research needs to take the initiative with an approach ISSN: 2722 -4015 http://ijstm.inarah.co.id to customer experience issues that have emerged as new challenges and will continue to present themselves.…”
Section: Introductionmentioning
confidence: 99%
“…to do research, why the big name Panasonic, which has been present in Indonesia for a long time, can't boost its high market share gain, can only stay in the top 5 positions. In fact, Panasonic has entered the electronic market in Indonesia earlier than other brands.Marketing managers in retail organizations usually devote time and effort to analyze the right promotions and products to maintain customer loyalty, so that the organization can be positioned properly in the market [3]. Sometimes, other research needs to take the initiative with an approach ISSN: 2722 -4015 http://ijstm.inarah.co.id to customer experience issues that have emerged as new challenges and will continue to present themselves.…”
Section: Introductionmentioning
confidence: 99%
“…An e-retailer can send only sensory and digital information, which is a significant factor in the existence of physical retail organizations in emerging markets as still, many consumers use the offline channel for shopping (Asmare & Zewdie, 2022;Chopra, 2016;Lin et al, 2022;Yin et al, 2022). The omnichannel structure is not creating all the capabilities in each channel but rather assigns products and tasks to channels on the basis of effective handling (Chen et al, 2014;Chen et al, 2022). This structure is more appropriate in emerging markets where interim retailing models such as Borders and Circuit way…”
Section: Omnichannel Retailing In Emerging Marketsmentioning
confidence: 99%
“…The literature review has identified seven main enablers and ten critical barriers exhibited in Table 2. The enablers are supporting OCR to enhance the customer's experience during purchase, including internet accessibility (Wang, 2013;Yu et al, 2016), Internet-enabled distribution centers (Chatterjee et al, 2002;Chen et al, 2014), Efficient and extensive logistics (Chen et al, 2022;Yan and Pei 2011;Blázquez, 2014), Customer analytics (Chatterjee et al, 2002), Visibility to customers (Agatz et al, 2008;Bahn & Fischer, 2003;Berman & Thelen,2018;Cassab & MacLachlan, 2009), Product digitization (Bernon et al, 2016;Verhoef et al, 2015), and integration (channel types, channel agents, and channel stages) (Saghiri et al, 2017). whereas the barriers are restricting the customer to use omnichannel including Low coordination among channel partners (Fulgoni, 2014;Hübner et al, 2016;Picot-Coupey et al, 2016), Variation in Pricing (Shankar et al, 2003;Neslin et al, 2006;Verhoef et al, 2015), Product Unavailability (Bernon et al, 2016;Chopra, 2016;Hübner et al, 2016;Ishfaq et al, 2022;Huang & Jin, 2020), Inconsistent contents (Verhoef et al, 2015), Central product (Balasubramanian et al, 2005;Verhoef et al, 2015), Data Security issues (Piotrowicz & Cuthbertson 2014) and Non-Understanding young customer habits (Verhoef et al, 2015), Order fulfillment (Chopra, 2016), Inconsistent Product discount (Sousa & Voss, 2006), and Time Constraint (Picot-Coupey et al, 2016;…”
Section: Research Gapsmentioning
confidence: 99%
“…It is considered a crucial business opportunity (Blom et al, 2021), enhancing consumer shopping experiences and increasing operational efficiency and sales (Cao and Li, 2015;Picot-Coupey et al, 2016;Timoumi et al, 2022). Consumers perceive cross-channel consistency in terms of product, service, price and promotion (Cao and Li, 2015;Chen et al, 2022;Hur e et al, 2017). Specifically, product consistency refers to the consistency in product assortment, descriptions, specifications and quality.…”
Section: Theoretical Background 21 Cross-channel Consistencymentioning
confidence: 99%
“…, 2022). Consumers perceive cross-channel consistency in terms of product, service, price and promotion (Cao and Li, 2015; Chen et al. , 2022; Huré et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%